Inside Cover: An Organotrifluoroborate for Broadly Applicable One‐Step 18F‐Labeling (Angew. Chem. Int. Ed. 44/2014). Issue 44 (5th September 2014) - Liu, Zhibo; Pourghiasian, Maral; Radtke, Mark Alex; Lau, Joseph; Pan, Jinhe; Dias, Gemma M.; Yapp, Donald; Lin, Kuo‐Shyan; Bénard, Francois; Perrin, David M.
<x xml:space="preserve">Abstract</x> Time is the essence for 18F labeling. The poor reactivity of aqueous fluoride ions has long been a challenge in 18F labeling. In their Communication on page 11876 ff., D. M. Perrin et al. present trifluoroborate–peptide conjugates that are labeled by isotopic exchange in water within 15 minutes to provide 18F tracers with high specific activity. Time‐consuming HPLC can be avoided. Several bioactive ligands enable PET imaging of in vivo targets.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>